Renal Denervation Attenuates Neuroinflammation in the Brain by Regulating Gut-Brain Axis in Rats With Myocardial Infarction - Huo, Jun-Yu; Jiang, Wan-Ying; Lyu, Yi-Ting; Zhu, Lin; Liu, Hui-Hui; Chen, Yuan-Yuan; Chen, Meng; Geng, Jie; Jiang, Zhi-Xin; Shan, Qi-Jun (Frontiers in Cardiovascular Medicine, 2021)
Aims: The development of neuroinflammation deteriorates the prognosis of myocardial infarction (MI). This study aimed to investigate the effect of renal denervation (RDN) on post-MI neuroinflammation in rats and the related mechanisms. Methods and results: Male adult Sprague-Dawley rats were subjected to sham or ligation of the left anterior descending coronary artery to induce MI. One week later, the MI rats received a sham or RDN procedure. Their cardiac functions were analyzed by echocardiography and their intestinal structures, permeability and inflammatory cytokines were tested. The intestinal microbiota were characterized by 16S rDNA sequencing. The degrees of neuroinflammation in the brains of rats were analyzed for microglia activation, inflammatory cytokines and inflammation-related signal pathways. In comparison with the control rats, the MI rats exhibited impaired cardiac functions, intestinal injury, increased intestinal barrier permeability and microbial dysbiosis, accompanied by increased microglia activation and pro-inflammatory cytokine levels in the brain. A RDN procedure dramatically decreased the levels of renal and intestinal sympathetic nerve activity, improved cardiac functions and mitigated the MI-related intestinal injury and neuroinflammation in the brain of MI rats. Interestingly, the RDN procedure mitigated the MI-increased intestinal barrier permeability and pro-inflammatory cytokines and plasma LPS as well as ameliorated the gut microbial dysbiosis in MI rats. The protective effect of RDN was not significantly affected by treatment with intestinal alkaline phosphatase, but significantly reduced by L-phenylalanine treatment in MI rats. Conclusions: RDN attenuated the neuroinflammation in the brain of MI rats, associated with mitigating the MI-related intestinal injury.